The Role of Factor Content in Trade Have Changes in Factor Endowments Been Reflected in Trade Patterns and on Relative Wages? - Stone, Susan (OECD Publishing, 2011)
The pattern of trade analysed from a factor content perspective reflects the relative factor endowments of the countries examined. Although some large economies, such as the United States, seem to exhibit counter-intuitive behaviour, this is reversed when intermediate trade is taken into account. We argue this is a reflection of the changing nature of production processes and trade. The evidence presented here implies factor endowments are undergoing changes that call for careful analysis of the measures commonly used in trade. Acknowledging the role of intermediate goods to understand a country's factor content trade position is one step. Additionally, one must account for the interaction between the domestic determination of employment and wages with international movement of goods and services, and location of tasks
Keywords: Trade